Prevalence of Hypertension and its Associated Factors among the Rural Population of Pakhribas Municipality in Eastern Nepal - Sharma, Khem Raj; Neupane, Aakash; Rayamajhi, Anusha; Pandey, Sandip (Med Phoenix, 2025)
Introduction: Hypertension (HTN) is a leading cause of preventable mortality globally, with an estimated 46% of the affected people unaware of their condition. Higher burden of HTN has been reported from the limited studies conducted among rural communities. Lifestyle, diet and healthcare access differ between urban and rural populations predisposing them to a greater burden. This study was conducted to assess the prevalence of HTN among the population of a rural Municipality and identify factors associated with it. Materials and methods: A community based cross-sectional study was conducted after ethical approval. Participants included the residents of all the 10 wards of Pakhribas Municipality with sample proportionate to population size. Pearson Chi-square tests and logistic regression analysis was done at 95 % CI for analysis. Results: The study found a high prevalence of HTN (33.9%) in the rural community and older age, male sex, self-reported salt consumption and body mass index (BMI) were factors significantly associated. Conclusion: The findings of this study highlight a higher burden of HTN in rural community and call for further investigations on the urban-rural differences in HTN to plan for provision of services as per the identified community needs.